Nonlinear Integral Inequalities in Two Independent Variables and Their Applications. (5th November 2007) - Zheng, Kelong; Wu, Yu; Deng, Shengfu
Abstract : This paper generalizes results of Cheung and Ma (2005) to more general inequalities with more than one distinct nonlinear term. From our results, some results of Cheung and Ma (2005) can be deduced as some special cases. Our results are also applied to show the boundedness of the solutions of a partial differential equation.